Cytotoxicity of drugs injected into joints in orthopaedics. Issue 2 (February 2019) - Busse, P.; Vater, C.; Stiehler, M.; Nowotny, J.; Kasten, P.; Bretschneider, H.; Goodman, S. B.; Gelinsky, M.; Zwingenberger, S.
Abstract : Objectives: Intra-articular injections of local anaesthetics (LA), glucocorticoids (GC), or hyaluronic acid (HA) are used to treat osteoarthritis (OA). Contrast agents (CA) are needed to prove successful intra-articular injection or aspiration, or to visualize articular structures dynamically during fluoroscopy. Tranexamic acid (TA) is used to control haemostasis and prevent excessive intra-articular bleeding. Despite their common usage, little is known about the cytotoxicity of common drugs injected into joints. Thus, the aim of our study was to investigate the effects of LA, GC, HA, CA, and TA on the viability of primary human chondrocytes and tenocytes in vitro . Methods: Human chondrocytes and tenocytes were cultured in a medium with three different drug dilutions (1:2; 1:10; 1:100). The following drugs were used to investigate cytotoxicity: lidocaine hydrochloride 1%; bupivacaine 0.5%; triamcinolone acetonide; dexamethasone 21-palmitate; TA; iodine contrast media; HA; and distilled water. Normal saline served as a control. After an incubation period of 24 hours, cell numbers and morphology were assessed. Results: Using LA or GC, especially triamcinolone acetonide, a dilution of 1:100 resulted in only a moderate reduction of viability, while a dilution of 1:10 showed significantly fewer cell counts. TA and CA reduced viability significantly at a dilution of 1:2. Higher dilutions did not affect viability. Notably, HA showed no effects of cytotoxicity in all drug dilutions. Conclusion: The toxicity of common intra-articular injectable drugs, assessed by cell viability, is mainly dependent on the dilution of the drug being tested. LA are particularly toxic, whereas HA did not affect cell viability. Cite this article : P. Busse, C. Vater, M. Stiehler, J. Nowotny, P. Kasten, H. Bretschneider, S. B. Goodman, M. Gelinsky, S. Zwingenberger. Cytotoxicity of drugs injected into joints in orthopaedics. Bone Joint Res 2019;8:41–48. DOI: 10.1302/2046-3758.82.BJR-2018-0099.R1.